Semi-Commercial and Traditional Hunting of Baar Tribe in Riung, Flores, East Nusa Tenggara - Kayat Kayat; Satyawan Pudyatmoko; Muhammad Ali Imron; Muchammad Maksum (Graduate Program, 2017)
ABSTRACTHunting is one of the aspects that influence number of wild animals. The article aims at describing semi-comercial and traditional hunting concept of Baar Tribe in East Nusa Tenggara as an alternative for wild animal conservation. The data collection methods are guided interview, in-depth interview and participant observation. The findings show that in the semi-comercial and traditional hunting concept of Baar Tribe in East Nusa Tenggara, traditional wisdom is represented by hunting techniques and equipments. It is likely that rapid semi-commercial hunting conducted by certain members of Baar tribe causes sharp decline in the population of wild animals. On the other hand, annual traditional hunting which strictly follows traditional code of conduct can maintain Timor deer population in Timor.Keywords: hunting, population, semi-commercial, traditional, Timor deer